Site-selective multi-porphyrin attachment enables the formation of a next-generation antibody-based photodynamic therapeutic. Issue 83 (4th September 2015) - Maruani, Antoine; Savoie, Huguette; Bryden, Francesca; Caddick, Stephen; Boyle, Ross; Chudasama, Vijay
Abstract : A next-generation antibody-based photodynamic therapeutic is assembled and shown to be potent and selective in vitro . Abstract : Herein we present a significant step towards next-generation antibody-based photodynamic therapeutics. Site-selective modification of a clinically relevant monoclonal antibody, with a serum-stable linker bearing a strained alkyne, allows for the controlled Cu-free "click" assembly of an in vitro active antibody-based PDT agent using a water soluble azide porpyhrin.